Smoking behavior and psychological dynamics during COVID-19 social distancing and stay-at-home policies: A survey - Caponnetto, Pasquale (Health Psychol Res, 2020)
During the COVID-19 pandemic, about 60 million of Italians stayed at home. These circumstances may generate exceptional challenges and stress for people who regularly use cigarettes, ecigarettes, heated tobacco products, dual users, former smokers and never smokers. Here, we present results from a study that was aimed at surveying smoking behaviour and psychological dynamics during the Italian COVID-19 social distancing and stay-at-home policies. Participants living in Italy were invited to complete an online brief questionnaire. A questionnaire was prepared and uploaded in an online survey tool. They were asked to participate regardless of their current smoking status and were divided in seven subgroups. In total, 1825 participants were included in the analysis. Exclusive cigarette smokers; Dual users of cigarette and ecigarettes; Dual users of cigarette and heated tobacco products; Former smokers; Exclusive users of e-cigarette; Exclusive users of heated tobacco products; never smoker. Dual users of cigarette and e-cigarette and exclusive cigarette smokers perceived that their daily consumption has slightly decreased. Exclusive cigarette smokers and exclusive e-cigarette users changed the way of purchasing products. Most exclusive cigarette smokers have considered quitting but most exclusive e-cigarette users have not considered stopping the use of e-cigarettes. In former smokers’ group, about one third of participants declared thoughts about starting to smoke again and in never smokers’ group few participants declared intention to start smoking. The COVID-19 era could be considered a “transition” phase and as such requires a search for a new balance. These changes in everyday habits can be a significant moment to use established and emerging strategies to create a definitive smoke-free world.